Physico-Chemical Engineering and Evaluation of Microstructures and Coatings for Solid-State Battery Composite Cathodes - Kissel, Maximilian; Justus Liebig University Giessen (My University, 2025)
Solid-state batteries are widely regarded as a key technology for next-generation energy storage, promising improved safety and higher energy densities. However, their widespread adoption remains hindered by fundamental challenges in materials development, interface stability, and cell processing. This dissertation addresses the often overlooked interplay between physico–electrochemical understanding and process engineering, with a focus on composite cathodes and cathode active material coatings. Unlike conventional lithium-ion batteries, where a liquid electrolyte infiltrates a porous electrode structure, solid-state batteries require the solid electrolyte to be directly integrated into the cathode composite during its fabrication. As a result, the mixing of the composite components becomes critical. Using a representative model system comprising a nickel-rich active material, a sulfide solid electrolyte, and a carbon additive, this thesis demonstrates that the quality of the mixing process has a direct impact on the electrochemical performance and reproducibility. Specifically, a method is validated and evaluated to quantify the static active material utilization in the composite as a microstructural descriptor, enabling a clear distinction between static and kinetic capacity losses. This allows for the quantification of mixing quality during process development and helps to avoid misinterpretation of capacity data in early-stage research. Based on this, a scalable mechanofusion process is investigated to create mixed-conducting matrix coatings as cathode microstructures. These coatings enable microstructural control and enhance electrochemical performance by facilitating both ionic and electronic transport across interfaces with intimate contact. In a complementary study, protective coatings on nickel-rich cathode active material particles using the model coating precursor Li3PS4 are investigated. A single annealing parameter is shown to significantly influence the coating’s composition, morphology, and ultimately the performance of the entire cell. These findings underscore how variations in processing conditions have major consequences on interphase properties and interfacial stability. To address this parameter space, a practical and efficient benchmarking protocol is developed that combines surface characterization and targeted electrochemical testing, focusing on impedance analysis. This reliable approach enables a systematic screening and an accelerated optimization of cathode coating strategies. The physico-chemical concepts and process strategies developed in this dissertation are broadly transferable to other material systems. They provide a robust framework for accelerated development and reliable evaluation of composite cathodes and coatings for solid-state batteries — on a fundamental level of materials research as well as toward industrial research.
Keywords: solid state batteries; protective coatings; cathode composites; particle processing; ddc:621.3; ddc:540